2020
DOI: 10.1002/clc.23344
|View full text |Cite
|
Sign up to set email alerts
|

Four‐year incidence of major adverse cardiovascular events in patients with atherosclerosis and atrial fibrillation

Abstract: Background: There is a paucity of contemporary data assessing the implications of atrial fibrillation (AF) on major adverse cardiovascular events (MACE) in patients with or at high-risk for atherosclerotic disease managed in routine practice. Hypothesis:We sought to evaluate the 4-year incidence of MACE in patients with or at risk of atherosclerotic disease in the presence of AF.Methods: Using US MarketScan data, we identified AF patients ≥45 years old with billing codes indicating established coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…A study using MarketScan claims data demonstrated in a cohort of 77 752 with coronary artery disease or at least three risk factors, and NVAF, of whom 48% had diabetes, that AF patients receiving an oral anticoagulant (OAC) compared to patients without OAC, were less likely to experience major adverse cardiovascular evnts (MACE) (8.9% vs 11.6%, P < 0.0001) including ischaemic stroke (5.4% vs. 6.7%, P < 0.0001). 22 In another study using MarketScan claims data for a cohort of only type 2 diabetes with non-valvular AF (NVAF), 10 700 users of the NOAC rivaroxaban and 13 946 users of warfarin were identified. The study found rivaroxaban was associated with a 25% (95% CI 4–41) reduced risk of MACE compared to warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…A study using MarketScan claims data demonstrated in a cohort of 77 752 with coronary artery disease or at least three risk factors, and NVAF, of whom 48% had diabetes, that AF patients receiving an oral anticoagulant (OAC) compared to patients without OAC, were less likely to experience major adverse cardiovascular evnts (MACE) (8.9% vs 11.6%, P < 0.0001) including ischaemic stroke (5.4% vs. 6.7%, P < 0.0001). 22 In another study using MarketScan claims data for a cohort of only type 2 diabetes with non-valvular AF (NVAF), 10 700 users of the NOAC rivaroxaban and 13 946 users of warfarin were identified. The study found rivaroxaban was associated with a 25% (95% CI 4–41) reduced risk of MACE compared to warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…Для пациентов старческого возраста с ФП характерно увеличение риска не только инсульта, но и других сердеч нососудистых осложнений, обусловленных атеросклеро зом. Наблюдение за 77752 пациентами с диагностирован ным атеросклерозом или факторами его риска и ФП в те чение 4 лет позволило установить, что суммарный риск тяжелых сердечнососудистых осложнений (сердечносо судистая смерть, инфаркт миокарда, ишемический инсульт) повышался по мере увеличения количества баллов по шкале CHA 2 DS 2 VASc [28]. Это указывает на предпочтительное проведение антикоагулянтной терапии, способной преду преждать не только инсульт, но и коронарные осложнения.…”
Section: фп и коморбидные состояния: какие есть возможности для всесторонней защиты пациента при применении антикоагулянтной терапии?unclassified
“…Рисунок 3. Частота развития СС событий 1 у пациентов с ФП и атеросклеротическим заболеванием или факторами риска атеросклероза 2 [28] ОБЗОРЫ § на преимущество ПОАК, относящихся к ингибиторам фактора Xa.…”
Section: антикоагулянтная терапия и гериатрические синдромыunclassified
“…По данным ретроспективного анализа Miao B, et al, у пациентов с ФП и ишемической болезнью сердца, заболеванием периферических артерий или инсультом/ТИА в анамнезе по мере увеличения суммы баллов по шкале оценки риска кровотечения у больных с ФП CHA 2 DS 2 -VASc (Congestive Heart failure, Hypertension, Age (2 ball), Diabetes mellitus, Stroke (2 ball), Vascular disease, Age, Sex category) увеличивался не только риск инсульта, но и других сердечно-сосудистых осложнений, в т.ч. инфарк та миокарда (ИМ) [28]. По данным метаанализа, включившего в себя данные 4 регистрационных РКИ по применению ПОАК при ФП (n=6206), оказалось, что причи-ной смерти у пациентов с ФП являются не столько инсульты или кровотечения (суммарная частота этих событий не превышает 12%), сколько осложнения заболеваний сердца (внезапная сердечная смерть/ жизнеопасные нарушения ритма, хроническая сердечная недостаточность, ИМ), которые составили 46% от всех причин летальных исходов [29].…”
Section: проблемы выбора антикоагулянта для вторичной профилактики инсульта у пациентов с фибрилляцией предсердийunclassified